KEBIJAKAN LEMBAGA SWADAYA MASYARAKAT AKSI CEPAT TANGGAP DALAM MENGATASI PANDEMI COVID-19 DI BALI (Jurnal Nawala Politika, 2023)
The COVID-19 pandemic spread very quickly, causing many fatalities, not only in Indonesia but in all countries in the world. Efforts to anticipate and mitigate the COVID-19 pandemic in each country are different. Aksi Cepat Tanggap (ACT) is a non-governmental organization that is active in social humanitarian concerns and is one of the government's efforts to prevent COVID-19 from spreading more widely. By using a descriptive qualitative method, this study also tries to find out how the ACT policy is dealing with the COVID-19 pandemic in Bali. The results of this study indicate that this activity is carried out through the 4P stages which consist of Purpose, People, Process and Performance. One example of an activity as its implementation is the social humanitarian institution, the ACT Bali Foundation, which helps Balinese people affected by COVID-19 by raising and distributing direct assistance to residents known as “Bangkit Bangsaku Bangkit Baliku”. Keywords : COVID-19 pandemic, non-governmental organizarion, Aksi Cepat Tanggap.